The Association Between Work-Family Conflict and Job Burnout Among Correctional Staff: A Preliminary Study - Lambert, Eric (American journal of criminal justice, 2010)
Working in corrections can be a demanding career in which work-family conflict and job burnout are possible. This study examined the relationship of the different forms of work-family conflict (time-based conflict, strain-based conflict, behavior-based conflict, and family on work conflict) with job burnout. Multivariate analysis of survey results from 160 staff who worked at a private Midwestern correctional facility for youthful offenders indicated that strain-based conflict, behavior-based conflict, and family on work conflict all had positive associations with job burnout. Time-based conflict had a non-significant relationship with job burnout.